The influence of the external and internal environment of primary care facilities on the prevention of diseases of the circulatory system - Kremsar, I. M.; Klymenko, V. I.; Кремсарь, Ірина Миколаївна; Клименко, Вікторія Іванівна (My University, 2021)
The aim: Of the work is analysis of strengths and weaknesses, opportunities and threats of the external and internal environment in primary care facilities for the implementation of preventive measures of cardiovascular diseases (CVDs). Materials and methods: An analysis of the work of primary health care facilities for the prevention of CVDs, which included external and internal audit, such as analysis of the regulatory framework, human resources, logistics provision, questionnaire of adult population of Zaporozhye region on awareness of factors risk of diseases of the circulatory system and a healthy lifestyle. Results: Thanks to the adoption of a number of regulations, timely management decisions, it was possible to achieve 100% provision of medical equipment necessary for the prevention of CVDs, but low staff capacity of doctors with their unsatisfactory level of knowledge about the main CVDs risk factors. instability, pose a serious threat to the further stable development of primary health care and their prevention. Conclusions: Significant progress had been made in the implementation of preventive measures for CVDs. Against the background of many existing problems.
Keywords: primary health care; cardiovascular diseases; prevention; threats; opportunities